At What Level (and in Whom) We Trust - Fulmer, C. Ashley; Gelfand, Michele J. (Journal of Management, 2012)
Despite the importance of trust across multiple levels in organizations, extant reviews have focused predominantly on trust at the individual level. A systematic review of trust research across levels and trust referents is sorely needed to synthesize the growing number of both micro and macro studies on this topic. Moreover, as trust is a linchpin for divergent areas, such as negotiation, leadership, team processes, human resource management, organizational change, entrepreneurship, and strategic alliances, a multilevel–multireferent review of trust can facilitate integration in the field of organizational sciences. In this review, the authors adopt a levels-of-analysis approach to organize the research on trust between 2000 and 2011 in multiple referents that include interpersonal, team, and organization at the individual, team, and organizational levels and analyze the similarities and differences in antecedents, consequences, and theoretical perspectives dominant at each level. Building on this foundation, the authors identify current strengths, weaknesses, and research gaps; offer recommendations for integration across levels and referents; and discuss lingering questions that research so far has overlooked. In doing so, the review offers a systematic and comprehensive view of the current state of the trust literature in organizational sciences and provides a blueprint for future research.